Efficacy of Topical 5% 5-Fluorouracil and 0.05% Tretinoin and Electrosurgery in the Treatment of Plane Warts: A Randomized Controlled Comparative Trial - Singh, Rashmi; Pandey, Shyam Sundar (Nepal Journal of Dermatology, Venereology & Leprology, 2021)
Human papilloma virus (HPV) is capable of causing varieties of dermatological conditions differing in morphology, histopathology and site of occurrence. Plane wart is one of the morphological varients accounting for approximately one fifth of HPV lesions. Treatment of plane warts is difficult and recurrence quite common .The objective of our study is to compare the efficacy and safety of 5% 5 –fluorouracil (5 FU),0.5% tretinoin and electrosurgery in the treatment of plane wart. Seventy five patients 38 males and 37 females were included in this randomized controlled comparative trial .Patients were age and sex matched and divided into three groups, GROUP A : Patients treated with 5% 5-Fluorouracil ,GROUP B:Patients treated with 0.5% tretinoin and GROUP C : Patients treated with electrodessication .While topical treatments were applied once nightly for 4 weeks(5% 5-fluorouracil for four hours and tretinoin overnight), radiodessication was done at first visit only.Result and conclusion:While radiofrequency showed faster results , results were more consistent with least recurrence in 5-FU and fair recurrence with .05% tretinoin.